FPGA BASED DIAGNOSIS AND CLASSIFICATION OF BREAST DISEASE USING THERMOGRAPHIC IMAGES - M2 ,T.Christy Bobby3, Gayathri. R1 , Vijaya Madhavi. (International Journal of Scientific Research and Management (IJSRM), 2017)
:The aim of this work is to detect breast cancer using thermographic Images. Mammogram is a very popular imagingmodality used for identifying breast cancer but fails to identify disease at an early stage, hence an emerging InfraRed(IR)technology known as thermogram is used for early stage detection. Clinical infrared thermography is a procedure that detects,records and produces images depending upon the variation of skin surface temperatures in the form of thermal patterns. Hencethermogram is an emerging technology to detect malignant breast conditions at early stage. Breast images acquired usingthermal IR camera is preprocessed and thresholding is performed to obtain skin tone images. Further the obtained processednormal and abnormal images are segmented and classified using skin color pixel classifier. Tools used for this work areMATLAB, Xilinx ISE design suite12 & Verilog. Database used is revised by confidently trained breast physicians.